Analysis of Influencer's Influence As Digital Marketing - Anik Yuliati; Syamsul Huda (Eduvest - Journal of Universal Studies, 2022)
Technology continues to develop and advance which has a major impact on everyday life including the online marketing process, one of which is by using social media influencers. An influencer is someone who acts as an bring another one because of their views, advice, or opinions so that they can influence buyers. This study aims to analyze the influence of influencers as digital marketing. This study uses a qualitative approach with a descriptive method, namely bt defining various matter being studied and then drawing conclusions. The results of the study show that influencers are carriers of influence in purchasing decisions so that influencers are used as the main choice in digital marketing strategies. Influencers use social media in their promotions. The social media that are widely used today are Instagram, TikTok, Facebook, Twitter, Pinterest, and so on. These influencers have influence with their honest reviews, in contrast to advertisements that openly bring viewers to buy their products